2001
DOI: 10.1079/bjn2000312
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient interactions: effects on absorption and bioavailability

Abstract: A potential risk of interactions between micronutrients affecting absorption and bioavailability has to be considered in any supplementation or fortification strategy. At levels of essential micronutrients present in foods, most micronutrients appear to utilise specific absorptive mechanisms and not be vulnerable to interactions. In aqueous solutions and at higher intake levels competition between elements with similar chemical characteristics and uptake by nonregulated processes can take place. These interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(133 citation statements)
references
References 36 publications
2
111
1
16
Order By: Relevance
“…There appears to be an intriguing interrelation between copper, zinc and Iron in absorption and utilization. On one-hand supplementation of Iron has been reported to affect bio-availability of zinc and copper in iron deficiency anemia by inter element competition in the bowel, while on the other hand bio-availability of copper and iron is affected by zinc supplementation and the impact is reflected in their blood levels (18,25,26). In view of this it becomes important that the judicious supplementation of micronutrients during pregnancy especially in iron deficiency anemia is essential to maintain their optimum blood levels required for the proper growth of the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be an intriguing interrelation between copper, zinc and Iron in absorption and utilization. On one-hand supplementation of Iron has been reported to affect bio-availability of zinc and copper in iron deficiency anemia by inter element competition in the bowel, while on the other hand bio-availability of copper and iron is affected by zinc supplementation and the impact is reflected in their blood levels (18,25,26). In view of this it becomes important that the judicious supplementation of micronutrients during pregnancy especially in iron deficiency anemia is essential to maintain their optimum blood levels required for the proper growth of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Similar were the observations of other workers (15,16). Besides various inhibiting factors in vegetarian diet, over supplementation of Iron during pregnancy could also adversely affect absorption of zinc (17,18). Zinc is passively transferred from mother to fetus across the placenta (19) and there is also decreased zinc binding capacity of maternal blood during pregnancy which facilitates efficient transfer of zinc from mother to fetus resulting in an increase level of zinc in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…Sendo assim, a determinação do teor total do metal ingerido pelo organismo não possibilita traçar um perfil da eficiência de sua absorção. Técnicas de especiação química, como a extração seqüencial, podem auxiliar na avaliação da biodisponibilidade dos minerais [9,20,23].…”
Section: Extração Seqüencial De Cobre Ferro E Zinco Em Ervas Medicinunclassified
“…The interaction between zinc and calcium or iron is of interest. Although the long-term use of calcium supplements has limited effect on the zinc status (Sandström 2001), old literature reports that the content of calcium in the diet might affect zinc absorption from phytate-containing meals (Oberleas et al 1966). Ellis et al (1987) have shown that this interference is dependent on the balance between calcium and phytate in the diet: the phytate × calcium/zinc millimolar ratios ≤200 is recommended in order to obtain an adequate zinc bioavailability from human diets.…”
Section: Interaction Of Zinc-calciummentioning
confidence: 99%